Serum kinetics of Calloselasma rhodostoma (Malayan pit viper) venom components in a rabbit - Tan, N.H.; Ponnudurai, G.; Fung, Shin Yee (BMC, 2009)
The serum kinetics of Calloselasma rhodostoma (Malayan pit viper) venom specifically two of its components, the major hemorrhagin (rhodostoxin) and a thrombin-like enzyme was examined in a rabbit by double-sandwich enzyme-linked immunosorbent assay (ELISA). The animal received intramuscularly a 1.0-mg/kg dose of C. rhodostoma venom. The venom level in serum peaked 12 hours after the injection, followed by a gradual decline and finally reached low rates 72 hours after administration. The serum kinetic profile of venom components, however, did not correspond to the profile of the whole C. rhodostoma venom. The serum levels of the C. rhodostoma thrombin-like enzyme increased slowly and peaked only 48 hours post-injection. Then both thrombin-like enzyme and rhodostoxin remained at relatively high levels 72 hours after administration. Data suggest that various venom components bind to tissue at the injection site with different affinities and that conjugated venom components were continuously released into circulation at different rates. The prolonged high serum levels of both thrombin-like enzyme and hemorrhagin are consistent with the clinical picture of prolonged clotting deficiency in severe cases of C. rhodostoma envenomation. Our results also suggest that since venom components are being released into and eliminated from the circulation at different rates, the "average composition" of the venom antigen in the circulation changes over time. This implies that data from ELISA quantification of antigen levels from serum venom employing "whole venom" as reagent must be interpreted with care.